44-Methylgambierone, a new gambierone analogue isolated from Gambierdiscus australes. Issue 8 (21st February 2019) - Murray, J. Sam; Selwood, Andrew I.; Harwood, D. Tim; van Ginkel, Roel; Puddick, Jonathan; Rhodes, Lesley L.; Rise, Frode; Wilkins, Alistair L.
Graphical abstract: Highlights: Novel secondary metabolite identified from Gambierdiscus australes . Isolation and purification protocols developed. NMR and MS experiments confirmed molecular structure as 44-methylgambierone. Compound previously identified as maitotoxin-3. Abstract: A new analogue of gambierone, 44-methylgambierone, was isolated from the benthic dinoflagellate Gambierdiscus australes collected from Raoul Island (Rangitahua/Kermadec Islands). This molecule has been previously reported as maitotoxin-3. The structure of 44-methylgambierone was elucidated using 1D- and 2D-nuclear magnetic resonance spectroscopy and mass spectrometry techniques. The nine-ring polyether backbone (A–I) and functional groups (carbonyl, terminal diol, 1, 3-diene and monosulphate) are the same for both compounds with the addition of an olefinic methyl group being the only modification in 44-methylgambierone.